PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA PETUGAS PADA DINAS PEMADAM KEBAKARAN KOTA SAMARINDA - Riskika, Riskika (OBOR: Oikonomia Borneo, 2019)
The purpose of this study was to determine how the effect of training and work discipline on the performance of officers at the Samarinda City Fire Department. This research is a research using quantitative descriptive method. Sources of data used in this study are primary data and secondary data, with data collection techniques in the form of observation, interviews, questionnaires. The sample in this study amounted to 117 respondents using the Slovin formula. The statistical method used in this study is multiple linear regression analysis using SPSS version 23. The results of this study show that partially the training variable has an effect but is not significant on the performance of firefighters in Samarinda City and the discipline variable has an effect and is significant on the performance of firefighters. Simultaneously training and work discipline have a significant effect on the performance of firefighters in Samarinda City. The value of Adjusted R Square is 0.492, which means that all independent variables can explain 49.2% of the dependent variable, while the remaining 50.8% can be explained by other factors not tested in this study.